2019
DOI: 10.1097/jnc.0000000000000062
|View full text |Cite
|
Sign up to set email alerts
|

Differentiated Antiretroviral Therapy Delivery: Implementation Barriers and Enablers in South Africa

Abstract: Scale-up of antiretroviral therapy (ART) for people living with HIV requires differentiated models of ART delivery to improve access and contribute to achieving viral suppression for 95% of people on ART. We examined barriers and enablers in South Africa via semistructured interviews with 33 respondents (program implementers, nurses, and other health care providers) from 11 organizations. The interviews were recorded, transcribed, and analyzed for emerging themes using NVivo 11 software. Major enablers of ART … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(53 citation statements)
references
References 19 publications
2
50
1
Order By: Relevance
“…Further research is merited to explore these issues in this setting. A reluctance to use fast-track queues by patients may be attributed to some clients still preferring to receive regular HIV care in clinical settings where they have established nurse/client relationships, receive regular health screening and can connect to other clients despite waiting and spending more time at the clinic (Sharer et al, 2019). Research from elsewhere in South Africa has also shown that post-partum women may avoid differentiated models of care if they are not in close proximity to health services for their infants (Myer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Further research is merited to explore these issues in this setting. A reluctance to use fast-track queues by patients may be attributed to some clients still preferring to receive regular HIV care in clinical settings where they have established nurse/client relationships, receive regular health screening and can connect to other clients despite waiting and spending more time at the clinic (Sharer et al, 2019). Research from elsewhere in South Africa has also shown that post-partum women may avoid differentiated models of care if they are not in close proximity to health services for their infants (Myer et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For those eligible and attending a CAC, the less frequent visit requirement of CACs (see Table 1) and ability to send a treatment 'buddy' to collect ART may aid WLH who are working or who would be unable to come to the clinic as regularly [40]. This flexibility is appreciated by those in CACs [8,40]. Integrated Care has the benefit of prolonging the time that the mother-infant pair are kept together which may limit (at least initially) the loss to follow up during transfer to another model [41].…”
Section: Discussionmentioning
confidence: 99%
“…The International AIDS (acquired immunodeficiency syndrome) Society categorises ART service delivery into four main types: 'facility-based individual models'; 'out-of-facility individual models'; 'healthcare worker-managed groups'; and 'clientmanaged groups' [6,7]. Some examples of specific ART delivery models within these four broad categories are as follows: fast track systems for ART collection within clinics such as in Malawi; community pharmacy collection in Nigeria; pick up points outside of healthcare facilities in the Democratic Republic of the Congo; collection by family members in Zimbabwe; teen ART clubs in Malawi and Swaziland; community adherence clubs in South Africa; and ART care integrated with other healthcare services such as for depression as is being studied in Malawi and Zimbabwe [6,[8][9][10][11][12][13][14]. WHO and UNICEF particularly recommend supporting the adherence of mothers during the postpartum period as part of the third and fourth part, of a four-component strategic approach to the prevention of mother-to-child transmission of HIV (PMTCT) [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…(2018 , 2019a , 2019b) have published a significant body of work on the programme theories underlying the ‘adherence club’ intervention, exploring how this intervention mitigates the relationship clients have with the health service and their treatment. Research by Bell et al (2019) explores men’s life context and how both the psychological and practical aspects of this context affects their access to HIV testing and treatment, and a study by Sharer et al (2019) discusses how codification of the 2016 National Adherence Guidelines by health services enabled HIV care that was flexible and which thereby facilitated differentiated, client-centred care.…”
Section: Review Strengths and Limitationsmentioning
confidence: 99%